Chronic intermittent haemofiltration and haemodialysis in end stage chronic heart failure with oedema refractory to high dose frusemide. - Dormans, T. P. (1996)
OBJECTIVE: To assess the benefits and problems of chronic intermittent treatment with haemofiltration or haemodialysis or both in patients with severe chronic heart failure (New York Heart Association class III or IV) and oedema refractory to pharmacological treatment. DESIGN AND SETTING: A retrospective case-cohort study. A general hospital in The Netherlands. PATIENTS: The results of chronic intermittent treatment with haemofiltration (n = 10) or haemodialysis (n = 2) were analysed in patients with severe chronic heart failure, predominantly due to coronary heart disease, and oedema refractory to a pharmacological regimen including high dose frusemide. INTERVENTION: Patients had an average of 25 (SD 38) treatments. RESULTS: There was improvement of NYHA class IV to III in seven patients. However, this was not reflected in a decrease in hospital admission: only two patients could be managed as outpatients. The median survival after start of the treatment was 24 days (varying from 0 to 393 days). In four patients the treatment was discontinued after discussion with the patient and family. CONCLUSIONS: The use of chronic intermittent haemofiltration and haemodialysis is of limited value in end stage chronic heart failure with oedema, refractory to maximal conventional treatment.